The Effect Of Using a Proposed Strategy According to The Constructivist Theory In Developing The Dialogue Literacue Among Students Of The fourth Literary Grade In the Subject of Sociology - Sultan, Abdul Rahman A.; Khudhair, Laila K. (Journal of Tikrit University for Humanities, 2023)
The aim of the research is to identify the effect of using a proposed strategy according to the constructivist theory in developing the culture of dialogue among the students of the fourth literary grade in the subject of sociology. The pre and post measurements of the scores of the experimental group in the measure of the culture of dialogue, the research sample consisted of (60) students from the fourth literary grade in the Assyrian Preparatory School for Boys affiliated to the General Directorate of Education of Salah al-Din / Shirqat Department,and they were distributed to Two groups (experimental and control), for each group (30) students, applied the experiment in the first semester of the academic year 2021-2022 AD, and the achievement test was applied to the two research groups, and the data was collected and analyzed statistically, and the result was in favor of the experimental group that studied the proposed strategy. It is attributed to the employment of constructivist theory in building the proposed strategy and its use in teaching sociology subject, making the curriculum simplified and understandable, which provides students with interest in a subject and enhances their positive role in the lesson.